Diabetic macular oedema: under‐represented in the genetic analysis of diabetic retinopathy - Broadgate, S; Kiire, C; Halford, S; Chong, V (John Wiley & Sons Ltd, 2018)
Diabetic retinopathy, a complication of both type 1 and type 2 diabetes, is a complex disease and is one of the leading causes of blindness in adults worldwide. It can be divided into distinct subclasses, one of which is diabetic macular oedema. Diabetic macular oedema can occur at any time in diabetic retinopathy and is the most common cause of vision loss in patients with type 2 diabetes. The purpose of this review is to summarize the large number of genetic association studies that have been performed in cohorts of patients with type 2 diabetes and published in English‐language journals up to February 2017. Many of these studies have produced positive associations with gene polymorphisms and diabetic retinopathy. However, this review highlights that within this large body of work, studies specifically addressing a genetic association with diabetic macular oedema, although present, are vastly under‐represented. We also highlight that many of the studies have small patient numbers and that meta‐analyses often inappropriately combine patient data sets. We conclude that there will continue to be conflicting results and no meaningful findings will be achieved if the historical approach of combining all diabetic retinopathy disease states within patient cohorts continues in future studies. This review also identifies several genes that would be interesting to analyse in large, well‐defined cohorts of patients with diabetic macular oedema in future candidate gene association studies.